2022
DOI: 10.3389/ti.2022.10397
|View full text |Cite
|
Sign up to set email alerts
|

Using Information Available at the Time of Donor Offer to Predict Kidney Transplant Survival Outcomes: A Systematic Review of Prediction Models

Abstract: Statistical models that can predict graft and patient survival outcomes following kidney transplantation could be of great clinical utility. We sought to appraise existing clinical prediction models for kidney transplant survival outcomes that could guide kidney donor acceptance decision-making. We searched for clinical prediction models for survival outcomes in adult recipients with single kidney-only transplants. Models that require information anticipated to become available only after the time of transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The current prediction models of graft outcome at the time of transplantation, however, have been criticized for being inaccurate and biased to disregard competing risks and the effect of allocation policy between donor and recipients. 6,13 KDPI utilization, while designed to counteract the nonuse of higherrisk transplants, has caused concern on the labeling effect of "high-KDPI" kidneys which are often at risk of nonuse. 10 High KDPI, long cold ischemia time, high creatinine level, and unfavorable biopsy results can all lead to organ nonutilization.…”
Section: Discussionmentioning
confidence: 99%
“…The current prediction models of graft outcome at the time of transplantation, however, have been criticized for being inaccurate and biased to disregard competing risks and the effect of allocation policy between donor and recipients. 6,13 KDPI utilization, while designed to counteract the nonuse of higherrisk transplants, has caused concern on the labeling effect of "high-KDPI" kidneys which are often at risk of nonuse. 10 High KDPI, long cold ischemia time, high creatinine level, and unfavorable biopsy results can all lead to organ nonutilization.…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, deceased donor kidneys vary substantially along a quality spectrum that portends highly differential expected graft longevity depending on donor age, medical history, etc . The decision to accept any particular kidney for any specific patient involves consideration of two key risks—graft failure and disease transmission (15)—along with tremendous uncertainty in how things will turn out for any given case (16,17), and it may very well be the most complex decision in all of medicine (18).…”
Section: Three Fundamental Realitiesmentioning
confidence: 99%
“…We sought to validate the predictive performance of the KDRI in the UK kidney transplantation population. In our systematic review [6], we found that the KDRI has been validated in different populations across the globe [7][8][9][10][11][12][13][14][15]. In the UK, Watson et al [14] assessed its performance in transplants performed between 2000 and 2007.…”
Section: Introductionmentioning
confidence: 98%